Thermosetting resin composition, molding material for fiber-reinforced composite material and fiber-reinforced composite material
The thermosetting resin composition, combining isocyanate and epoxy resins with specific catalysts and sulfonamide compounds, addresses the challenges of injection time and curing in fiber-reinforced composites, achieving stable viscosity, complete impregnation, and improved heat resistance.
Patent Information
- Application Number
- JP2023164179
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
Existing thermosetting resin compositions made from isocyanate compounds face challenges in ensuring adequate injection time during molding of thick fiber-reinforced composite materials, leading to incomplete impregnation and deformation issues due to rapid curing and high reactivity.
A thermosetting resin composition comprising an isocyanate compound, epoxy resin, a catalyst such as a quaternary onium salt or inorganic salt, and sulfonamide compounds, which balances viscosity stability during injection with rapid curing, ensuring complete impregnation and improved heat resistance.
The proposed composition achieves excellent viscosity stability during injection, allowing for complete impregnation of fibers and rapid curing, resulting in fiber-reinforced composite materials with enhanced heat resistance and reduced deformation issues.
Smart Images

Figure 2025054937000001 
Figure 2025054937000002 
Figure 2025054937000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermosetting resin composition that is preferably used for aerospace parts and general industrial applications, and to a molding material for a fiber-reinforced composite material and a fiber-reinforced composite material each using the same. [Background technology]
[0002] Thermosetting resins made from isocyanate compounds are characterized by excellent heat resistance, fracture toughness, and adhesiveness due to the formation of rigid isocyanurate rings by isocyanate homopolymerization. Taking advantage of these characteristics, these thermosetting resins are used in various fields such as paints, adhesives, foams, and elastomer materials. Among them, thermosetting resins made from isocyanate compounds and epoxy resins generate rigid oxazolidone rings in addition to the formation of isocyanurate rings, and in addition to the above characteristics, they also have excellent moisture and heat resistance, so they are expected to be used in structural material applications, particularly fiber-reinforced structural materials.
[0003] There are various molding methods for producing such fiber-reinforced composite materials, but when a thermosetting resin is used as the matrix resin, injection molding methods such as the resin transfer molding method (RTM method) are generally used. When a thermosetting resin composition containing an isocyanate compound is used, the reactivity of the isocyanate group is high, so when the matrix resin is injected and impregnated into the fiber substrate in a heated mold, the curing proceeds and some of the resin does not impregnate, resulting in an underfilled molding material for fiber-reinforced composite materials. As can be seen from this result, the challenge of using a thermosetting resin composition made of an isocyanate compound is to ensure the injection time during molding. In particular, the structural materials used have become thicker in recent years, and the technical difficulty of ensuring the injection time has become higher than before. In addition, the isocyanate reacts with functional groups on the fiber surface or the surface of the secondary material, with release components on the surface of the molded plate, and with moisture in the molding material for the fiber-reinforced composite material or in the atmosphere, inhibiting the intended isocyanate homopolymerization, resulting in a fiber-reinforced composite material having less rigidity than designed, and the fiber-reinforced composite material being deformed by stress when being removed from a mold at a high temperature. Therefore, there has been a need to develop a technology for ensuring the injection time during molding of a thermosetting resin composition made of an isocyanate compound, and a technology for promoting the reaction between isocyanate groups to impart sufficient heat resistance to the cured thermosetting resin composition.
[0004] Patent Document 1 describes a thermosetting resin composition in which a carboxamide compound is added to a urethane prepolymer and an isocyanate compound. Patent Document 2 describes a thermosetting resin composition in which DBU is added as a catalyst to an isocyanate compound and an epoxy resin. Patent Document 3 describes a thermosetting resin composition consisting of a polyvinyl chloride resin, an isocyanate compound, an epoxy resin, and a conductive filler. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2012 / 103965 [Patent Document 2] JP 2016-526063 A [Patent Document 3] China Patent Application Publication No. 112662090 Summary of the Invention [Problem to be solved by the invention]
[0006] The thermosetting resin composition described in Patent Document 1 has excellent long-term storage stability at room temperature due to the addition of carboxamide, but when heated and injected in RTM molding of a thick fiber-reinforced composite material, the thermosetting resin composition gels in a short time, causing underfill at the ends of the fiber-reinforced composite material. In addition, the obtained fiber-reinforced composite material is deformed when demolded at the molding temperature, so this technology remains insufficient.
[0007] The thermosetting resin composition described in Patent Document 2 gels in a short time when heated and injected during RTM molding of a thick fiber-reinforced composite material due to the addition of DBU, causing underfill at the ends of the fiber-reinforced composite material. In addition, the resulting fiber-reinforced composite material deforms when demolded at the molding temperature, and this remains an insufficient technique.
[0008] The thermosetting resin composition described in Patent Document 3 is a blend of polyvinyl chloride resin and conductive filler, and when heated and injected during RTM molding of a thick fiber-reinforced composite material, the resin viscosity is high, the injection time is long, and workability is poor. In addition, the thermosetting resin composition gels in a short time, causing underfill at the ends of the fiber-reinforced composite material. In addition, the obtained fiber-reinforced composite material is deformed when demolded at the molding temperature, and this technology remains insufficient. [Means for solving the problem]
[0009] The present inventors have an object to provide a thermosetting resin composition which overcomes the above-mentioned drawbacks of the conventional art, and a fiber-reinforced composite material using the same.
[0010] In order to solve the above problems, the present invention has the following configuration. [1] A thermosetting resin composition containing the following components (A) to (D), wherein the content of component (A) in the thermosetting resin composition is 30% by mass or more and 99% by mass or less, and the thermosetting resin composition satisfies the following formula (1). Component (A): Isocyanate compound Component (B): Epoxy resin Component (C): Catalyst Component (D): Sulfonamide compound represented by formula (I)
[0011]
Chemical formula
[0012] (In the formula, R1 is selected from the group consisting of a substituted or unsubstituted linear or branched alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group, and an aryl ring. R2 is selected from the group consisting of a hydrogen atom and a substituted or unsubstituted linear or branched alkyl group having 1 to 10 carbon atoms.) 2.1 < Mh / Me ≤ 100 ··· Formula (I) Mh: The number of moles of isocyanate groups contained in component (A) Me: The number of moles of epoxy groups contained in component (B) [2] The thermosetting resin composition according to [1], wherein the content of component (D) in the thermosetting resin composition exceeds 0.11% by mass and is 5% by mass or less. [3] The thermosetting resin composition according to [1] or [2], wherein component (C): The catalyst contains a quaternary onium salt and / or an inorganic salt. [4] The epoxy resin composition according to any one of [1] to [3], wherein the content of component (C) in the thermosetting resin composition is 0.1% by mass or more and 5% by mass or less. [5] The thermosetting resin composition according to any one of [1] to [4], wherein component (A) is an aromatic isocyanate. [6] The thermosetting resin composition according to any one of [1] to [5], wherein the viscosity of the thermosetting resin composition after 1 hour at 60°C after preparation is 0.01 Pa·s or more and 1.00 Pa·s or less. [7] A molding material for a fiber-reinforced composite material, comprising the thermosetting resin composition according to any one of [1] to [6] and reinforcing fibers. [8] The molding material for a fiber-reinforced composite material according to [7], wherein the content of the reinforcing fibers is 40% by mass or more and 90% by mass or less. [9] The molding material for a fiber-reinforced composite material according to [7] or [8], wherein the reinforcing fiber is a carbon fiber.
[10] A fiber-reinforced composite material obtained by heat curing the molding material for a fiber-reinforced composite material according to any one of [7] to [9]. Effect of the Invention
[0013] According to the present invention, it is possible to provide a thermosetting resin composition that has excellent viscosity stability during injection when molding a thick fiber-reinforced composite material and has excellent heat resistance after curing. In addition, by using such a thermosetting resin composition, It is possible to provide a molding material for a fiber-reinforced composite material in which the thermosetting resin composition is sufficiently impregnated into a substrate. Furthermore, by using the molding material for a fiber-reinforced composite material, it is possible to provide a fiber-reinforced composite material that is thicker than conventional fiber-reinforced composite materials, which can be used in high-speed RTM molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Preferred embodiments of the present invention will be described below. First, the thermosetting resin composition of the present invention will be described.
[0015] The thermosetting resin composition of the present invention is a thermosetting resin composition comprising the following components (A) to (D), wherein the content of component (A) in the thermosetting resin composition is 30 mass% or more and 99 mass% or less, and the thermosetting resin composition satisfies the following formula (1): Component (A): Isocyanate compound Component (B): Epoxy resin Component (C): Catalyst Component (D): A sulfonamide compound represented by formula (I)
[0016] [ka]
[0017] (In the formula, R1 is selected from the group consisting of a substituted or unsubstituted linear or branched alkyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group, and an aryl ring. R2 is selected from the group consisting of a hydrogen atom and a substituted or unsubstituted linear or branched alkyl group having 1 to 10 carbon atoms.) 2.1 < Mh / Me ≤ 100 ··· Formula (1) Mh: The number of moles of isocyanate groups contained in component (A) Me: The number of moles of epoxy groups contained in component (B).
[0018] Component (A) in the present invention is an isocyanate compound. Such an isocyanate compound is not particularly limited as long as it is a compound having an isocyanate group in the molecule. By reacting the isocyanate group with the epoxy group of component (B) by heat curing to form a rigid oxazolidone ring structure, the molded product exhibits excellent heat and moisture resistance and toughness.
[0019] As such an isocyanate compound, for example, aromatic isocyanates, aliphatic isocyanates, alicyclic isocyanates, etc. can be used. Among them, aromatic isocyanates containing an aromatic group in the molecular skeleton are preferably used because they have excellent curing reactivity and exhibit excellent heat resistance.
[0020] Examples of isocyanate compounds preferably used in the present invention include aliphatic isocyanates such as hexamethylene diisocyanate and 1,2,3,4-tetraisocyanate butane, p-phenylene diisocyanate, tolylene diisocyanate, diphenyl-4,4-diisocyanate, benzene-1,2,4-triisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate (MDI), diphenylpropane diisocyanate, tetramethylene xylene diisocyanate, and polymethylene polyphenyl polyisocyanate, and alicyclic isocyanates such as cyclohexane diisocyanate, isophorone diisocyanate, lysine diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isopropylidenedicyclohexyl diisocyanate. These isocyanate compounds may be used alone or in combination of two or more.
[0021] Examples of commercially available aliphatic isocyanates that can be used include HDI (manufactured by Tosoh Corporation), Duranate (registered trademark) D101, and Duranate (registered trademark) D201 (all manufactured by Asahi Kasei Corporation).
[0022] Commercially available aromatic isocyanates include, for example, "Rupranate (registered trademark)" MS, "Rupranate (registered trademark)" MI, "Rupranate (registered trademark)" M20S, "Rupranate (registered trademark)" M11S, "Rupranate (registered trademark)" M5S, "Rupranate (registered trademark)" T-80, "Rupranate (registered trademark)" MM-103, "Rupranate (registered trademark)" MM-102, and "Rupranate (registered trademark)" MM-301 (all manufactured by BASF INOAC Co., Ltd.). Polyurethane Co., Ltd.), "Millionate (registered trademark)" MT, "Millionate (registered trademark)" MT-F, "Millionate (registered trademark)" MT-NBP, "Millionate (registered trademark)" NM, "Millionate (registered trademark)" MR-100, "Millionate (registered trademark)" MR-200, "Millionate (registered trademark)" MR-400, "Coronate (registered trademark)" T-80, "Coronate (registered trademark)" T-65, "Coronate (registered trademark)" T-100 (all manufactured by Tosoh Corporation), "Cosmonate (registered trademark)" PH, "Cosmonate (registered trademark)" M-50, "Cosmonate (registered trademark)" T-80 (all manufactured by Mitsui Chemicals, Inc.), etc. can be used.
[0023] Commercially available alicyclic isocyanates include, for example, "Takenate (registered trademark)" 600 (manufactured by Mitsui Chemicals, Inc.) and "Fortimo (registered trademark)" 1,4-H6XDI (manufactured by Mitsui Chemicals, Inc.).
[0024] The content of component (A) in the thermosetting resin composition must be 30% by mass or more and 99% by mass or less. By making the content of component (A) 30% by mass or more, preferably 55% by mass or more, excellent viscosity stability can be exhibited during injection when molding a thick fiber-reinforced composite material. In addition, by making the content of component (A) 99% by mass or less, preferably 95% by mass or less, a thermosetting resin composition having excellent heat resistance after curing can be provided.
[0025] The component (B) in the present invention is an epoxy resin. Such an epoxy resin is not particularly limited as long as it is a compound having an epoxy group in the molecule. For example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, amine type epoxy resin, aliphatic epoxy resin, etc. can be mentioned. The epoxy resin may be used alone or in combination of two or more kinds.
[0026] Commercially available bisphenol A type epoxy resins that can be used include, for example, jER (registered trademark) 825 and jER (registered trademark) 828 (both manufactured by Mitsubishi Chemical Corporation), Epotohto (registered trademark) YD-128 and Epotohto (registered trademark) YD-8125 (both manufactured by Nippon Steel Chemical & Material Co., Ltd.), DER (registered trademark) 331 and DER (registered trademark) 332 (both manufactured by The Dow Chemical Company), and the like.
[0027] Commercially available bisphenol F type epoxy resins that can be used include, for example, jER (registered trademark) 806, jER (registered trademark) 807, jER (registered trademark) 4004P (all manufactured by Mitsubishi Chemical Corporation), EPICLON (registered trademark) 830 (manufactured by DIC Corporation), Epototo (registered trademark) YD-170, Epototo (registered trademark) YDF-8170C (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), and the like.
[0028] Examples of the amine-type epoxy resin used in the present invention include tetraglycidyldiaminodiphenylmethane, triglycidylaminophenol, diglycidylaniline, and the like.
[0029] Examples of the aliphatic epoxy resin used in the present invention include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, polyethylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether.
[0030] Examples of commercially available aliphatic epoxy resins that can be used include "Denacol (registered trademark)" EX-810, "Denacol (registered trademark)" EX-841, "Denacol (registered trademark)" EX-211, "Denacol (registered trademark)" EX-212, "Denacol (registered trademark)" EX-214, "Denacol (registered trademark)" EX-252, and "Denacol (registered trademark)" EX-931 (all manufactured by Nagase ChemteX Corporation), "ADEKA GLYCIROL (registered trademark)" ED-503, "ADEKA GLYCIROL (registered trademark)" ED-523, and "ADEKA GLYCIROL (registered trademark)" ED-506 (all manufactured by ADEKA Corporation).
[0031] In the thermosetting resin composition of the present invention, the value (Mh / Me) obtained by dividing the number of moles (Mh) of isocyanate groups contained in component (A) by the number of moles (Me) of epoxy groups contained in component (B) is in the range of more than 2.1 and not more than 100. The range is preferably more than 4 and not more than 45, and more preferably more than 4 and not more than 30. By setting it in such a range, even when other functional groups are present, the reaction between the epoxy resin and the isocyanate compound is not inhibited and the reaction between the isocyanates proceeds sufficiently, so that the cured product of the obtained thermosetting resin composition can be imparted with sufficient heat resistance and rigidity.
[0032] The number of moles (Mh) of isocyanate groups contained in component (A) is the sum of the masses of the respective isocyanate compounds divided by the active isocyanate equivalents of the respective isocyanate compounds, and is expressed by the following formula. Mh = (mass of isocyanate compound A of component (A) / active isocyanate equivalent of isocyanate compound A of component (A)) + (mass of isocyanate compound B of component (A) / active isocyanate equivalent of isocyanate compound B of component (A)) + + (mass of isocyanate compound W of component (A) / active isocyanate equivalent of isocyanate compound W of component (A)).
[0033] The number of moles (Me) of epoxy groups contained in component (B) is the sum of the number of moles of each epoxy resin active group and is represented by the following formula. Me = (mass of epoxy resin A / epoxy equivalent of epoxy resin A) + (mass of epoxy resin B / epoxy equivalent of epoxy resin B) + + (mass of epoxy resin W / epoxy equivalent of epoxy resin W).
[0034] Component (C) in the present invention is a catalyst. In the present invention, the catalyst promotes the curing reaction between the epoxy groups of component (B) and the isocyanate groups of component (A). By adding such a catalyst, the oxazolidone cyclization reaction proceeds preferentially, and a fiber-reinforced composite material having excellent fracture toughness, deformation ability, and moist heat resistance of the cured product can be obtained.
[0035] Examples of catalysts preferably used in the present invention include imidazole compounds, tertiary amine compounds, heterocyclic amine compounds, imidazolium salts, quaternary onium salts, inorganic salts, etc. These catalysts may be used alone or in combination of two or more kinds.
[0036] Commercially available imidazole compounds that can be used include, for example, Curazol (registered trademark) 2E4MZ, Curazol (registered trademark) 2PZ, Curazol (registered trademark) 2P4MZ, and Cureduct (registered trademark) P-0505 (all manufactured by Shikoku Kasei Co., Ltd.), and 1-methylimidazole (manufactured by Tokyo Kasei Kogyo Co., Ltd.).
[0037] Examples of commercially available tertiary amine compounds that can be used include triethylamine, tributylamine, triphenylamine, and N,N-dimethylbenzylamine (all manufactured by Tokyo Chemical Industry Co., Ltd.).
[0038] Examples of commercially available heterocyclic amine compounds that can be used include 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,5-diazabicyclo[4.3.0]-5-nonene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,4-diazabicyclo[2.2.2]octane, 4-dimethylaminopyridine, and 4-aminopyridine (all manufactured by Tokyo Chemical Industry Co., Ltd.).
[0039] Examples of commercially available imidazolium salts that can be used include 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium iodide, 1-hexyl-3-methylimidazolium bromide, and 1-hexyl-3-methylimidazolium chloride (all manufactured by Tokyo Chemical Industry Co., Ltd.).
[0040] Examples of commercially available quaternary ammonium salts that can be used include benzyltrimethylammonium chloride, benzyltrimethylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium iodide, tetrapropylammonium bromide, tetrapropylammonium chloride, and tetrapropylammonium iodide (all manufactured by Tokyo Chemical Industry Co., Ltd.).
[0041] Commercially available quaternary phosphonium salts that can be used include, for example, "TBP-BB (registered trademark)", "TPP-PB (registered trademark)", "TPP-MB (registered trademark)", "TPP-EB (registered trademark)", and "TPP-IPI (registered trademark)" (all manufactured by Hokko Sangyo Co., Ltd.), (2-hydroxy-5-methylphenyl)triphenylphosphonium bromide, and 1-ethyl-3-methylimidazolium bromide (all manufactured by Tokyo Chemical Industry Co., Ltd.).
[0042] Examples of inorganic salts include alkali metal salts, alkaline earth metal salts, first transition metal salts, etc. Examples of commercially available inorganic salts that can be used include calcium chloride, calcium bromide, calcium iodide, magnesium chloride, magnesium bromide, magnesium iodide, potassium chloride, potassium bromide, potassium iodide, sodium chloride, sodium bromide, sodium iodide, lithium chloride, lithium bromide, and lithium iodide (all manufactured by Tokyo Chemical Industry Co., Ltd.).
[0043] Here, the thermosetting resin composition of the present invention preferably contains a quaternary onium salt or an inorganic salt as component (C). The inorganic salt is a salt composed of a cation made of an inorganic substance, typically a metal element, and an anion derived from a base. By containing an inorganic salt as component (C), the curing time can be shortened. In particular, since the thermosetting resin composition can be cured in a wide temperature range from 50°C to 200°C, it is preferable to contain an alkali metal halide as component (C). When a quaternary onium salt, typically a quaternary ammonium salt or a quaternary phosphonium salt, is used, it can be preferably used since it exhibits high heat resistance and mechanical properties.
[0044] Furthermore, the thermosetting resin composition of the present invention more preferably contains a quaternary onium salt and an inorganic salt simultaneously as component (C). By containing a quaternary onium salt and an inorganic salt simultaneously, a fast curing property that cannot be achieved by an inorganic salt alone is expressed. This effect is presumably due to the quaternary onium salt promoting the catalytic activation action of the inorganic salt.
[0045] The content of component (C) in the thermosetting resin composition is preferably 0.1% by mass or more and 5% by mass or less. By making the content of component (C) 0.1% by mass or more, preferably 1.0% by mass or more, the target fiber reinforced composite material can be obtained in a shorter curing time. In addition, by making the content of component (C) 5% by mass or less, a thermosetting resin composition having excellent heat resistance after curing can be obtained.
[0046] The component (D) in the present invention is a sulfonamide compound represented by the following formula (I).
[0047] [ka]
[0048] (In the formula, R1 is selected from the group consisting of substituted or unsubstituted linear or branched alkyl groups having 1 to 10 carbon atoms, substituted or unsubstituted cycloalkyl groups, and aryl rings. R2 is selected from the group consisting of a hydrogen atom, and substituted or unsubstituted linear or branched alkyl groups having 1 to 10 carbon atoms).
[0049] The thermosetting resin composition of the present invention exhibits excellent latency, which cannot be achieved by only the components (A), (B), and (C), by including the component (D). Specifically, the thermosetting resin composition exhibits viscosity stability at the heating temperature to which it is exposed in the resin injection process. In addition, the composition exhibits rapid curing properties, in which the reaction proceeds rapidly. Generally, viscosity stability and rapid curing properties are in a trade-off relationship, and it is difficult to simultaneously achieve both properties, but the thermosetting resin composition of the present invention can simultaneously achieve the above properties. This is believed to be because the inclusion of the component (D) inhibits for a certain period of time the reaction between the epoxy group and the isocyanate group, which is promoted by the component (C), and the polymerization reaction between the isocyanate groups themselves. This is a remarkable effect that can only be achieved by the sulfonamide compound represented by formula (I), and it is necessary that at least one hydrogen atom is covalently bonded to the nitrogen atom in the sulfonamide bond.
[0050] The content of component (D) in the thermosetting resin composition is preferably more than 0.11% by mass and not more than 5% by mass. By having the mass ratio of component (D) exceed 0.11% by mass, preferably exceed 1.0% by mass, it is possible to impart better latency. In addition, by having the mass ratio of component (D) be not more than 5% by mass, it is possible to obtain a thermosetting resin composition having excellent heat resistance after curing.
[0051] It is preferable that the viscosity of the thermosetting resin composition after heating to 60°C for 1 hour after preparation is 0.01 Pa·s or more and 1.00 Pa·s or less. When the viscosity is 0.01 Pa·s or more, the desired thick fiber reinforced composite material can be obtained with a shorter injection time. Furthermore, when the viscosity is 1.00 Pa·s or less, a thermosetting resin composition having excellent heat resistance after curing can be obtained. The viscosity can be measured according to <Measurement of viscosity of thermosetting resin composition> described below.
[0052] The molding material for fiber-reinforced composite material of the present invention is not particularly limited as long as it contains reinforcing fibers and the thermosetting resin composition of the present invention, and may be in a state in which the reinforcing fibers are impregnated with the thermosetting resin composition or in a state in which the reinforcing fibers are not impregnated with the thermosetting resin composition. In addition, the thermosetting resin composition may be in an unreacted state or in a state in which it has partially reacted and become B-stage.
[0053] In the molding material for fiber-reinforced composite material, the content of reinforcing fibers is preferably in the range of 40% by mass or more and 90% by mass or less. If the content of reinforcing fibers is 40% by mass or more, the mass of the obtained fiber-reinforced composite material is not excessively large, and the advantages of the fiber-reinforced composite material having excellent specific strength and specific elastic modulus are easily exhibited. In addition, if the content of reinforcing fibers is 90% by mass or less, the impregnation of the thermosetting resin composition into the reinforcing fibers is excellent.
[0054] The fiber-reinforced composite material of the present invention is not particularly limited as long as it contains reinforcing fibers and a molded article obtained by heat-curing the thermosetting resin composition of the present invention. However, it is preferable that the fiber-reinforced composite material is obtained by heat-curing the molding material for the fiber-reinforced composite material.
[0055] In the present invention, glass fibers, aramid fibers, carbon fibers, boron fibers, etc. are preferably used as reinforcing fibers. Among them, carbon fibers are preferably used because they can provide a fiber-reinforced composite material that is lightweight yet has excellent mechanical properties such as strength and elastic modulus.
[0056] The reinforcing fibers may be either short fibers or continuous fibers, or a combination of both. In order to obtain a fiber-reinforced composite material having excellent mechanical properties and a high reinforcing fiber mass content, continuous fibers are preferred.
[0057] When the reinforcing fibers are used in a continuous form, examples of the fibers include long fibers aligned in one direction, single tows, woven fabrics, knitted fabrics, nonwoven fabrics, mats, braided cords, and other fiber structures, and the average fiber diameter is preferably 3 μm or more and 12 μm or less.
[0058] In the fiber-reinforced composite material of the present invention, the reinforcing fibers may be used in the form of strands, but a substrate made of reinforcing fibers processed into a form such as a mat, woven fabric, knit, braid, unidirectional sheet, etc. is preferably used. Among these, a woven fabric is preferably used because it is easy to obtain a fiber-reinforced composite material with a high Vf and has excellent handling properties.
[0059] The method for molding the fiber-reinforced composite material is not particularly limited, but methods such as RTM (Resin Transfer Molding), film bag molding, pultrusion, and press molding, which have excellent productivity, are preferably used. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0061] <Resin raw materials> The components used in this embodiment are as follows: 1. Component (A): Isocyanate compound Polymeric MDI "Lupranate (registered trademark)" M20S (manufactured by BASF INOAC Polyurethanes Ltd.) 2. Component (B): Epoxy resin Bisphenol A type epoxy resin "jER (registered trademark)" 828 (manufactured by Mitsubishi Chemical Corporation) 3. Component (C): Catalyst N,N-Dimethylbenzylamine (Tokyo Chemical Industry Co., Ltd.) Lithium bromide (Tokyo Chemical Industry Co., Ltd.) Tetraphenylphosphonium bromide "TPP-PB (registered trademark)" (manufactured by Hokko Sangyo Co., Ltd.) 4. Component (D): A sulfonamide compound represented by formula (I) N-Ethyl-o / p-toluenesulfonamide "Topsizer (registered trademark)" No. 3 (manufactured by Fuji Amido Chemical Co., Ltd.) p-Toluenesulfonamide "Topsizer (registered trademark)" No. 1S (manufactured by Fuji Amido Chemical Co., Ltd.) 5. Plain woven fabric Made of Toray carbon fiber T800S-12K-50C, with a weight of 190g / m 2 A plain weave carbon fiber fabric was used.
[0062] <Method for preparing thermosetting resin composition> In a stainless steel beaker, component (B): epoxy resin, and component (D): sulfonamide compound represented by formula (I) were mixed and appropriately kneaded until each component was compatible to obtain an epoxy base liquid. In a separate container, component (A): isocyanate compound, and component (C): catalyst were added, and if necessary, heated to make them compatible to obtain a hardener liquid. A predetermined amount of epoxy base liquid and hardener liquid were mixed and kneaded with a planetary mixer for 3 minutes to obtain a thermosetting resin composition. The resin composition is as shown in Tables 1 to 3.
[0063] <Method of producing cured resin> The resin composition obtained according to the above <Method for preparing thermosetting resin composition> was degassed in a vacuum, and then heat-treated in a mold set to a thickness of 2 mm using a 2 mm Teflon (registered trademark) spacer at 150°C for 2 hours, and then heat-treated at 200°C for 2 hours to obtain a cured resin product with a thickness of 2 mm.
[0064] <Method of manufacturing fiber-reinforced composite materials> The plain woven base material cut to 395mm x 395mm was laminated in a mold having a 400mm x 400mm square plate-shaped cavity that can accommodate molded plate thicknesses up to 5mm, with the warp direction set to 0°, and four sheets were laminated in order from the bottom layer by repeating -45° / 0° / +45° / 90° once, and then four sheets were laminated in order from the bottom layer by repeating 90° / +45° / 0° / -45° once, for a total of eight sheets, which were then set in the mold, and the mold was clamped at 0.3MPa with a press device. Next, the mold temperature was kept at 50°C, and the pressure was reduced to atmospheric pressure -0.1MPa by a vacuum pump, and the epoxy resin composition obtained according to the above <Preparation method of thermosetting resin composition>, which had been preheated to 50°C, was injected at a pressure of 0.2MPa. The temperature was raised to 200°C at a rate of 5°C / min, and after 1 hour at 200°C, the mold was opened and the material was demolded to obtain a fiber-reinforced composite material.
[0065] <Measurement of Viscosity of Thermosetting Resin Composition> The complex viscosity (η*) of the thermosetting resin composition prepared according to the above <Preparation method of thermosetting resin composition> was measured using a dynamic viscoelasticity measuring device (ARES-G2: manufactured by TA Instruments) under the measurement conditions of a frequency of 1 Hz and a gap of 1.0 mm, using parallel plates with a diameter of 40 mm. In this case, the thermosetting resin composition immediately after preparation was placed on the parallel plates set at a measurement temperature of 60°C, and the η* obtained one hour later was taken as the viscosity of the thermosetting resin composition.
[0066] <Method for evaluating the degree of impregnation of a thick substrate with a resin composition> First, straw paper was set in a mold having a plate-shaped cavity of 400mm x 400mm square. Then, 24 plain woven substrates cut to 395mm x 395mm were laminated by repeating -45° / 0° / +45° / 90° six times from the bottom layer with the warp direction set to 0°, and 24 more were laminated by repeating 90° / +45° / 0° / -45° six times from the bottom layer, for a total of 48 laminated substrates. The mass of the resin composition obtained according to the above <Preparation method of thermosetting resin composition> was adjusted so that Vf was 50%, and the resin film was obtained by uniformly applying it to a 400mm x 400mm square area on the film. The obtained resin film was placed on the top surface of the laminate. At this time, the resin surface of the resin film was set in contact with the plain woven substrate and the resin composition was impregnated downward. After leaving it for 60 minutes under a condition of 25°C, the laminate was removed from the mold and it was confirmed whether the straw paper was impregnated with the resin composition. At this time, the impregnated area was rated as A when it was more than 80%, B when it was more than 60% but not more than 80%, and C when it was 60% or less.
[0067] <Method for evaluating the degree of demolding of fiber-reinforced composite materials at 200℃> The fiber-reinforced composite material obtained according to the above <Method of producing fiber-reinforced composite material> was placed on a flat surface. When the distance between one vertex of the rectangle of the fiber-reinforced composite material and the flat surface was set to 0 mm, the gaps between the vertices of the other three rectangles and the flat surface were measured. The three obtained values were summed to obtain the gap amount A. Next, the fiber-reinforced composite material was turned over and the same procedure was repeated to obtain the gap amount B. At this time, the case where the gap amount A and the gap amount B were both 3 mm or less was evaluated as A, the case where both were more than 3 mm and less than 6 mm, and the case where one was 3 mm or less and the other was more than 3 mm and less than 6 mm, and the case where either or both were more than 6 mm was evaluated as C.
[0068] (Examples 1 to 16) Thermosetting resin compositions and fiber-reinforced composite materials were prepared according to the above <Preparation of thermosetting resin compositions> and <Method of preparing fiber-reinforced composite materials> using the resin compositions shown in Tables 1 and 2. The degree of impregnation into the thick substrate and the degree of demolding of the fiber-reinforced composite materials at 200°C were evaluated according to the above evaluation methods. As a result, the degree of impregnation into the thick substrate was B or higher, and the degree of demolding of the fiber-reinforced composite materials at 200°C was B or higher, which were both good results.
[0069] (Comparative Examples 1 to 5) Thermosetting resin compositions and fiber-reinforced composite materials were prepared using the resin compositions shown in Table 3 according to the above <Preparation of thermosetting resin compositions> and <Method of preparing fiber-reinforced composite materials>. As per the above evaluation method, the degree of impregnation into the thick substrate and the demoldability of the fiber-reinforced composite material at 200°C were evaluated. As a result, both the degree of impregnation into the thick substrate and the demoldability of the fiber-reinforced composite material at 200°C were not B or higher and were poor.
[0070] [Table 1]
[0071] [Table 2]
[0072] [Table 3]
[0073] The units of each component in the table are parts by mass. [Industrial Applicability]
[0074] The thermosetting resin composition of the present invention has excellent viscosity stability during injection when molding thick fiber-reinforced composite materials, and excellent heat resistance after curing. Furthermore, the thermosetting resin composition provides a molding material for fiber-reinforced composite materials that is sufficiently impregnated into a substrate, and the molding material for fiber-reinforced composite materials is suitable for high-speed RTM molding, and is excellent in that it provides excellent quality to thick fiber-reinforced composite materials that have been difficult to mold compared to conventional ones. This leads to the application of fiber-reinforced composite materials in aerospace and automotive applications, as well as sports and industrial applications in general, which is expected to reduce energy consumption, mainly fossil fuels, and contribute to the problem of global warming.
Claims
1. A thermosetting resin composition comprising the following components (A) to (D), wherein the content of component (A) in the thermosetting resin composition is 30 mass% or more and 99 mass% or less, and the thermosetting resin composition satisfies the following formula (1): Component (A): Isocyanate compound Component (B): Epoxy resin Component (C): Catalyst Component (D): A sulfonamide compound represented by formula (I) 【Chemistry 1】 (In the formula, R 1 is selected from the group consisting of substituted or unsubstituted linear or branched alkyl groups having 1 to 10 carbon atoms, substituted or unsubstituted cycloalkyl groups, and aryl rings. 2 is selected from the group consisting of a hydrogen atom and a substituted or unsubstituted straight-chain or branched alkyl group having 1 to 10 carbon atoms. 2.1<Mh / Me≦100...Formula (1) Mh: The number of moles of isocyanate groups contained in component (A) Me: The number of moles of epoxy groups contained in component (B)
2. 2. The thermosetting resin composition according to claim 1, wherein the content of component (D) in the thermosetting resin composition is more than 0.11 mass% and 5 mass% or less.
3. Component (C): The thermosetting resin composition according to claim 1, which contains a quaternary onium salt and / or an inorganic salt as a catalyst.
4. 2. The epoxy resin composition according to claim 1, wherein the content of component (C) in the thermosetting resin composition is 0.1% by mass or more and 5% by mass or less.
5. 2. The thermosetting resin composition according to claim 1, wherein component (A) is an aromatic isocyanate.
6. 2. The thermosetting resin composition according to claim 1, wherein the thermosetting resin composition has a viscosity of 0.01 Pa·s or more and 1.00 Pa·s or less after 1 hour at 60° C. after preparation.
7. A molding material for a fiber-reinforced composite material, comprising the thermosetting resin composition according to claim 1 and reinforcing fibers.
8. The molding material for a fiber-reinforced composite material according to claim 7, wherein the content of the reinforcing fibers is 40% by mass or more and 90% by mass or less.
9. 9. The molding material for a fiber-reinforced composite material according to claim 7 or 8, wherein the reinforcing fibers are carbon fibers.
10. A fiber-reinforced composite material obtained by heat curing the molding material for a fiber-reinforced composite material according to claim 7 or 8.
Citation Information
Patent Citations
Modified rigid polyvinyl chloride foam and preparation method thereof
CN112662090A
isocyanate-epoxide hybrid resin
JP2016526063A
Epoxy resin composition
WO2012103965A1